Sequencing human rhinoviruses: Direct sequencing versus plasmid cloning - Linder, Jodell E. (2015)
Human rhinoviruses (RV) are associated with the majority of viral respiratory illnesses in infants, children and adults. Over the last several years, researchers have begun to sequence the many different species and strains of RV in order to determine if certain species were associated with increased disease severity. There are a variety of techniques employed to prepare samples for sequencing. One method utilizes plasmid-cloning, which is expensive and takes several hours to complete. Recently, some investigators have instead used direct sequencing to sequence RV strains, allowing for omission of the time- and labor-intensive cloning step. This study formally compares and contrasts the sequencing results obtained from plasmid-cloning and direct Sanger sequencing of a 500 base pair PCR product covering the VP4/VP2 region of RV. A slightly longer sequence (by 65 base pairs on average) was obtained when specimens were plasmid-cloned, and the sequences were 86% similar. After trimming the extra base pairs from the cloned sequences, the sequences were 99.7% identical. Overall success of directly sequencing samples was similar to that of cloning, 5% on average failed for each technique. Therefore, in many instances, directly sequencing samples may be considered in lieu of the more expensive and time-consuming plasmid-cloning technique.